Viabilitas Weissella confusa F213 Pada Sari Buah Terung Belanda (Solanum betaceanum Cav.) Terfermentasi dan Karakteristiknya Selama Penyimpanan - Simatupang, Irvan Kurniawan; Nocianitri, Komang Ayu; Kencana Putra, I Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i03.p10, 2023)
This research was conducted to knowing the storage time of fermented tamarillo juice with Weissella confusa F213 which still can be categorized as a probiotic drink and has good characteristics. This study used a completely randomized design (CRD) with factor treatment storage time of 0, 5, 10, 15, 20, 25, and 30 days. The treatment was repeated 3 times resulting in 21 experimental units and the data were analysed by analysis of variance followed by multiple comparison test of Duncan Multiple Range Test (DMRT). The results showed that probiotic tamarillo juice can still be categorized as a probiotic drink until 30 days of storage at cold temperatures (4oC) with good characteristics, namely total LAB 7.26 Log CFU / ml, total acid 0.379%, total sugar 15.49%, pH 4.1, TSS 10 oBrix, slightly preferred aroma and colour and preferred overall taste and acceptance.